Determinants of utilization of National Health Insurance Fund cover in public health facilities by public health care workers in Makueni County - Muia, Angeline M.; Njoroge, Kezia; Oluoch, Musa (International Journal Of Community Medicine And Public Health, 2022)
Background: Robust healthcare funding systems are seen as critical for guaranteeing universal healthcare access. This implies that health services should be adequately accessible to everyone ensuring health situation doesn’t reduce the patient and their family to poverty making analysis of determinants of National Health Insurance Fund (NHIF) cover utilization critical. Methods: Descriptive research design was used to study utilization of NHIF cover among health professionals in public hospitals in Makueni County. Stratified random sampling technique was used to sample the facilities across the different levels. The study sample was 291 from a target population of 1183 health professional. The data was collected using structured questionnaires. Statistical package for social science (SPSS version 25) was used to code and analyze the raw data. Pearson's coefficient of correlation and multiple regressions were used to assess the association between determinants and NHIF utilization. Results: The study found and concluded that at the significance level of 95%, alternative insurance covers, perceived quality of health services and NHIF communication strategy significantly influenced utilization of NHIF cover by public health care workers at α=0.05. On the other hand, NHIF scheme characteristic was an insignificant determinant of utilization of NHIF cover among public health care workers in Makueni County. Conclusions: The study concludes alternative insurance covers, NHIF scheme characteristics, perceived quality of health services influenced utilization of NHIF cover and NHIF communication strategy influenced utilization of NHIF cover among health workers.